Investigation of Molecular Size Effect on the Formation of Lignin Nanoparticles by Nanoprecipitation - Jae Hoon Lee; Shin Young Park; In-Gyu Choi; Joon Weon Choi (Applied Sciences, 2020)
In recent years, several studies focused on the synthesis of lignin-based nanoparticle in aqueous solution and its potential applications of the drug carrier were investigated. In this study, soda lignin (SL) nanoparticles (i.d. 128–560 nm) were synthesized by the nanoprecipitation process at three different concentrations (1, 2, and 4 mg/mL THF) with various molecular sizes of soda lignin (NP-F1, NP-F2, and NP-F3) obtained from sequential solvent extraction. The average molecular weights of SL, F1, F2, F3, F4, and F5 were 3130, 1190, 2550, 3680, 5310, and 14,650, respectively. The average size of the spherical lignin nanoparticle was a minimum of 128 nm for NP-C1 and the size increased up to 560 nm with increasing concentration. Particle surface charge increased with increasing concentration from −26 mV for NP-C1 to −38 mV for NP-C4. Contrary to expected general trends in polymeric nanoparticles, there was no remarkable change or trend with increasing lignin molecular weight since chemical structures of each lignin fraction are also remarkably different. Further studies to learn correlation between properties of lignin nanoparticle and its additional details regarding the chemical structures is needed.